Modelling of microbial polyhydroxyalkanoate surface binding protein PhaP for rational mutagenesis - Zhao, Hongyu (Microb Biotechnol, 2017)
Phasins are unusual amphiphilic proteins that bind to microbial polyhydroxyalkanoate (PHA) granules in nature and show great potential for various applications in biotechnology and medicine. Despite their remarkable diversity, only the crystal structure of PhaP(A) (h) from Aeromonas hydrophila has been solved to date. Based on the structure of PhaP(A) (h), homology models of PhaP(A) (z) from Azotobacter sp. FA‐8 and PhaP(TD) from Halomonas bluephagenesis TD were successfully established, allowing rational mutagenesis to be conducted to enhance the stability and surfactant properties of these proteins. PhaP(A) (z) mutants, including PhaP(A) (z)Q38L and PhaP(A) (z)Q78L, as well as PhaP(TD) mutants, including PhaP(TD)Q38M and PhaP(TD)Q72M, showed better emulsification properties and improved thermostability (6‐10°C higher melting temperatures) compared with their wild‐type homologues under the same conditions. Importantly, the established PhaP homology‐modelling approach, based on the high‐resolution structure of PhaP(A) (h), can be generalized to facilitate the study of other PhaP members.